Accountability in SME Islamic entrepreneurship during the Covid-19 pandemic / Rohmawati Kusumaningtias … [et al.] - Kusumaningtias, Rohmawati; Kamaluddin, Amrizah; Ismail, Aida Hazlin; Alias, Pujiono; Venusita, Lintang; Putra, Rediyanto (Universiti Teknologi MARA, 2021)
The impact of the Covid-19 pandemic due to the implementation of social-physical distancing has caused the economy to decline globally. Entrepreneurs have to adapt to business processes in a revolutionary manner. This study aimed to determine the accountability of Islamic entrepreneurs operating SMEs in dealing with the Covid-19 pandemic. This research used Jaatun’s (Jaatun, Pearson, Gittler, Leenes, & Niezen, 2016) conceptual framework as the initial basis for accountability. This research also used Husserl’s phenomenology to explore the experiences of entrepreneurs’ awareness, thoughts, and actions which are valued and accepted ethically by stakeholders. The results showed four elements of accountability: responsiveness, responsibility, appropriateness, and effectiveness. These four elements built accountability horizontally, which links the relationship between agents in the business process and vertically, representing SMEs’ awareness of God’s existence. Responsiveness revealed efforts to adapt while keeping health as the top priority. Responsibility delivered moral responsibility for business sustainability by redesigning the business processes. Appropriateness is an effort to present the best products through synergy and online marketing. Effectiveness showed product diversification. Vertically, entrepreneurs’ performance was based on gratefulness to God for guidance and strength. The entrepreneurs perceived that every business activity is an effort to help His creatures through their products.